Carbon Emission Disclosure dan Nilai Perusahaan - Sari, Kadek Heni Vitrya; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 32 No 1 (2022), 2022)
This study aims to obtain empirical evidence regarding the effect of carbon emission disclosures on company value in manufacturing companies on the IDX. The research uses stakeholder theory and legitimacy. The research population is all manufacturing companies listed on the IDX for the 2018-2019 period. The research sample is the annual report of manufacturing companies determined using purposive sampling technique. The data analysis technique used simple linear regression. The results of this study show that carbon emission disclosures have a positive effect on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2019. This means that the higher the disclosure of carbon emissions, the higher the value of the company. Keywords: Carbon Emission Disclosure; Company Value.